New prospects for the comparative linguistics development - Grishenkova E.S., Biryukova E.V.,; Skuratov I.V., Vasilyeva N.M., Maksimenko O.I., (Opción, 2020)
The purpose of this article is to determine whether comparative cultural linguistics is a separate direction in linguistics and what are the prospects for its further development via comparative qualitative research methods. As a result, a distinctive feature of the English language is that freedom is understood as a process in it, though the French language is the divine manifestation of freedom. In conclusion, the solution to such problems of clarification of formal coincidence at the internal divergence of the compared language units opens wide prospects of further development of comparative cultural linguistics.